(untitled) (Research, Society and Development, 2021)
The use of herbal medicines has grown considerably in recent years, due to the erroneous thought that products of plant origin are harmless, and therefore do not cause adverse effects or have drug interactions. The use of these drugs with oral contraceptives can bring risks to patients. The potential negative clinical effects that can be caused by these drug interactions must be emphasized to prevent risks and ensure the effectiveness of this contraceptive method that is one of the most used by women seeking to prevent pregnancy. The users of herbal medicines usually believe that herbal medicine is a therapeutic alternative free of adverse effects and/or incapable of causing drug interactions, but herbal medicines are composed of several chemical compounds, which, in turn, may be responsible for antagonistic and/or synergistic effects with other drugs. The main interactions that can occur with contraceptives are with popularly used herbal medicines such as licorice, alfalfa, cannabis, cimicifuga, St. John’s wort, ginseng, kava-kava, saw palmetto, sene, and soy. The herbal medicines have several chemical compounds, among which we highlight the secondary metabolites, responsible for the pharmacological actions and mechanism of action of drug interactions, which are often similar in plants that have in their composition the same metabolites, as in the case of saponins and isoflavones that reduce the speed of biotransformation of oral contraceptives.